Analysis of the Supply Chain of Local Beef Cattle Commodity and Beef in North Sulawesi - Eusebius K.M. Endoh; Jeane Pandey; Adrie Abram Sajow (International Journal of Applied Business and International Management, 2021)
The high price of local beef at the retail and end consumer levels is due to many members in the supply chain. As a result, the selling price is low at the producer level. The research aims to identify the state of production factors, analyze the product, financial information flows of the supply chain and the margin value of various distribution channels, and formulate a development strategy. The survey research with the case study model was conducted on 256 respondents with a qualitative descriptive analysis, network, supply chain distribution margins, and the formulation of strategies. The analysis results show that in North Sulawesi there are five distribution channels with varying margin values between 32.71-39.20 percent. This confirms that the supply routes for local beef and beef cattle commodities in North Sulawesi depress farmers' income and burden consumers. The development strategy is with an industrial approach from upstream to downstream.